Problem structuring and analysis method based on soft system methodology for teaching requirements engineering / Rafia Naz Memon - Memon, Rafia Naz (2014)

(untitled)
The discipline of Requirements Engineering (RE) is hard for students to understand and challenging for lecturers to teach due to its complex nature. In the literature, researchers have presented a number of Requirements Engineering Education (REE) problems in universities, as well as RE problems in the industry, which can be addressed by providing proper REE at universities. However, no effort has been made to systematically compile, and analyse these problems so that it is possible to have a bird’s-eye view of REE problems. This analysis and presentation of the problems is referred to as “an integrated view of the REE problems”. Some problems have been reported and investigated by researchers while some remain only as reported problems. Therefore, this research aims to come up with an integrated view of REE problems, followed by selecting one problem area to be the research focus and addressing the selected problem by formulating a method. In the first phase of the study, an integrated view of REE problems was produced. A survey was then performed among students and lecturers who have studied and taught RE course to verify the REE problems presented in the integrated view and to identify a selected research focus. This leads to the identification of the research focus which is teaching problem structuring and analysis. The literature survey on problem structuring and analysis showed that it has not been explicitly emphasised in the RE course but thought to be covered using requirements analysis methods. For students with no industrial experience, it is difficult to learn problem structuring and analysis using these methods. Therefore, in the second phase of the research, a light-weight method was proposed to be taught to undergraduate software engineering students in the RE course to enable them to understand and perform the problem structuring and analysis. The method is referred to as L-Soft to portray that it has transformed the idea of Soft system methodology into a light-weight iii (simple structure and easy to apply procedure) RE method. In order to facilitate the understanding and application of the L-Soft method, students were provided with a step-by-step guide on performing the problem structuring and analysis, a glossary of terms used in the method and a sample of solved case studies. A web-based tool for LSoft was developed to provide learning support to the students. In the final phase of the study, the appropriateness of the method for performing the problem structuring and analysis was validated using feature analysis performed by lecturers and software engineers. The perceived adoption in practice was validated using method acceptance testing performed by the lecturers and software engineers and the results showed that the L-Soft method has a high likelihood of being adopted in practice. Finally, an experimental study was performed among undergraduate software engineering students to validate the method’s successfulness. The results showed that LSoft was more efficient and effective than an existing analysis method and have a higher likelihood of being adopted into practice rather than the existing analysis method.